2021
DOI: 10.2196/19846
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain Integration With Digital Technology and the Future of Health Care Ecosystems: Systematic Review

Abstract: Background In the era of big data, artificial intelligence (AI), and the Internet of Things (IoT), digital data have become essential for our everyday functioning and in health care services. The sensitive nature of health care data presents several crucial issues such as privacy, security, interoperability, and reliability that must be addressed in any health care data management system. However, most of the current health care systems are still facing major obstacles and are lacking in some of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Research shows that the possibilities of telehealth aspect growth are huge but slowed down due to various barriers. The conditions and prospects for the technological development of telemedicine lie, among others, in access to smart devices, 5G network, and the Internet of Medical Things (IoMT), as well as many others [ 40 , 41 , 42 , 70 ]. To decrease the barriers to entry in privacy regulations and patient access to technology, concerted efforts are needed [ 35 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that the possibilities of telehealth aspect growth are huge but slowed down due to various barriers. The conditions and prospects for the technological development of telemedicine lie, among others, in access to smart devices, 5G network, and the Internet of Medical Things (IoMT), as well as many others [ 40 , 41 , 42 , 70 ]. To decrease the barriers to entry in privacy regulations and patient access to technology, concerted efforts are needed [ 35 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Block-chain plays a vital role in modern healthcare systems, and is considered to be one of the most transversal and promising technologies [ 74 , 75 , 76 ]. The data source, robustness, decentralized management, security, and privacy of the block-chain and the immutability of stored data are the main reasons why the block-chain attracts the attention of the healthcare industry [ 74 , 77 ]. Due to its technical characteristics, the application of block-chain in healthcare industry has provided some benefits, but there are also implementation and supervision problems.…”
Section: Research Topics and Evolution Analysismentioning
confidence: 99%
“…Forum et al [ 49 ] systematically explored blockchain technology and demonstrated two case studies to examine the role of blockchain in health care. Blockchain technology could be used in clinical trial management, such as smart-contract applications, participant-controlled data access, trustless protocols, and data validity.…”
Section: Introductionmentioning
confidence: 99%